Popkon Gila / Dzulqarnain Abdul Hakim - Abdul Hakim, Dzulqarnain (2021)
First and foremost, I'd like to express my gratitude to all of my friends for their assistance in completing my ENT work. Next, I'd want to express my gratitude to Madam Hazelen for her assistance in completing the second task. I then sold POPKON GILA items in the second duty. Alhamdulillah, my friends and neighbours in Hulu Perak have raved about this product. This product is something I sell because it has the potential to help people. It might let you relax and eat while you concentrate on your homework or watch a movie. Finally, I chose this product and sold it utilising the group promotion approach, and I was pleasantly surprised to discover that it had surpassed my aim of 150.00 ringgit.